Strain rate and curing condition effects on the stress–strain behaviour of epoxy adhesive materials. Issue 16 (18th August 2017) - Paul, Shiddartha; Motalab, Mohammad; Zobayer, Md. Ali; Hossain, Md. Jakir
Abstract: Adhesive materials evolve properties that change significantly with the preparation procedures and curing conditions. In this study the effects of curing conditions (curing time and temperature), and strain rate on the stress–strain behaviour of the commercially available Lapox epoxy adhesive materials have been evaluated experimentally. The rectangular test specimens have been prepared with different curing temperatures and times. After preparation, the specimens have been tested in small scale tensile testing machine to investigate the stress–strain behaviour at room temperature. It has been observed that as the curing time or curing temperature is increased, the ultimate tensile strength and the elastic modulus of the material also increase. A four parameter hyperbolic tangent model has been fitted to the experimental data and the model constants have been evaluated for different curing conditions and strain rates. Furthermore, for a fixed curing time and strain rate, empirical equations have been developed for modelling the dependence of curing temperature on the stress–strain curves. Finally, the developed equations have been implemented into the finite element analysis of a lap joint to investigate the stress and strain distributions of the adhesive layer for different curing conditions (curing time and temperature).